(untitled) (Journal of Comparative & International Higher Education, 2024)
The present paper aims to discuss higher education and the role of digital learning in the Brazilian context. In a social justice, multicultural perspective, it argues that effective digital learning in higher education is likely to happen when digital curricular contents have been embedded with inclusionary strategies that foster plural students’ critical thinking and empowerment. To develop the argument, it firstly discusses the multicultural nature of Brazilian society and the relevance of conceptualizing digital learning and multicultural perspectives in education. It then highlights the higher education system and structure in Brazil, discussing how remote digital learning has been taking place in that system. It also depicts how digital learning in higher education has been conceived in Brazilian educational policies, both before, and as a result of the pandemic time in 2020. It contends that digital learning has been faced with two differing concepts by the public and the private sector of Brazilian higher education, either in a transformative, multicultural approach, or in a consumer, massified perspective. Based on a multicultural, intersectional approach, it argues that for higher education to have a strong impact in preparing future professionals for dealing with the challenges of globalised and multicultural societies, it should link digital learning with multicultural, intersectional concerns that value cultural diversity and fight against prejudices and exclusion. In that sense, the Brazilian case can be useful comparatively, by illustrating the potentials and the challenges of digital learning in unequal, multicultural countries. Keywords: Brazil, comparative perspectives, digital era, higher education, multiculturalism